Molecular Profile of Trichophyton mentagrophytes and Microsporum canis based on PCR-RFLP of Internal Transcribed Spacer - Dwi Endrawati; Eni Kusumaningtyas (Jurnal Ilmu Ternak dan Veteriner, 2021)
Trichophyton mentagrophytes and Microsporum canis are dermatophytes fungi which commonly infect animal and human. Conventional and molecular methods were used for identification of the fungus. The region of internal transcribed spacer (ITS) has a high probability for fungal identification. PCR-RFLP was reported as a useful method to differentiate dermatophytes fungi. The objective of the study was to compare molecular profile of T. mentagrophytes and M. canis based on the result of ITS fragment digestion using Dde I, Hinf I and Mva I. The molds were isolated from skin scrapping of 18 animals which showed dermatophytosis lesion. The isolated molds were grown on agar plate for 14 days of incubation at 37oC and then identified based on macro and microscopic morphologies. Amplification of chitin synthase gene was used for confirmation and separation of dermatophytes from other fungi. ITS fragment was amplified and then digested using restriction enzymes Dde I, Hinf I and Mva I. The result showed that digestion products from ITS fragment of T. mentagrophytes and M. canis were different. The fragment 159 bp from Dde I, 374 bp from Hinf I and 89 bp from Mva I were present in T. mentagrophytes but absent in M. canis.   Based on these results, specific RFLP profile of digestion ITS region by Dde I, Hinf I and Mva I can be used as a specific marker for species of dermatophytes fungi.